Self-care practices and online student engagement during Covid-19 in the Philippines: A mixed methods study - Cleofas, Jerome V (Issues in educational research, 2021)
The Covid-19 pandemic and the transition of educational landscapes from traditional to online classes, have exposed students to an increased risk of mental health problems that can impact their educational engagement and learning outcomes. Self-care practices can help protect students from psychological challenges, and also improve student outcomes; however, the drastic societal changes brought about by quarantine and digital learning may cause disruptions in students' practice of self-care. The aim of this convergent mixed methods study is to determine the relationship between self-care practices and online student engagement, and describe the barriers in practising self-care among undergraduate students during the pandemic. An online survey was administered to a convenience sample of 202 students from De La Salle University, Philippines. Quantitative results suggest that specific domains of self-care practices are statistically linked with background characteristics and online student engagement. On the other hand, two themes describing the barriers to practising self-care emerged from the qualitative data: (1) quarantine-related barriers; and (2) online-class-related barriers.